Evaluation of twenty genotypes of wheat (Triticum aestivum L.) grown under heat stress during germination stage - Yasir MAJEED; Shaista FIAZ; Wan TENG; Adnan RASHEED; Syed F.A. GILLANI; Zhu XI; Mahmoud F. SELEIMAN; André A. DIATTA; Harun GITARI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2023)
Heat stress is one of the most devastating abiotic stresses which causes significant loss of agricultural crop productivity. Thus, it is critical to examine the wheat’s response to the heat stress at seedling stage and adopt an appreciated breeding method to develop heat tolerance and to avoid harmful effects. Therefore, twenty wheat genotypes, including two local landraces, were evaluated in the current study to investigate the genetic diversity for heat tolerance at the seedling stage. Grains of wheat genotypes were placed on filter papers in Petri dishes for germinating at different temperature ranges (i.e., 25 °C as control, 30 °C, 35 °C, and 40 °C). The experiment was laid out in a completely randomized design (CRD) with the factorial arrangement and the number of replications was three. Analysis of variance (ANOVA) for seedling traits and biochemical analysis showed that the genotypes had significant differences for coleoptile length, shoot length (SL), root length (RL), shoot fresh weight (SFW), vigor index (VI), glycine betaine (GB) and proline content. The effect of temperature treatments on different wheat genotypes also exhibited highly significant variation for VI. Principal component analysis (PCA) showed that four factors contributed 82.8% to total variability with the Eigen value greater than 0.7 at 35 °C. Correlation analysis showed that coleoptile length and germination percentage (GP) had a highly significant-positive correlation with SL, VI, and SFW. Results showed that wheat genotypes of ‘Maraj’, ‘Fareed’, ‘Darabi’, ‘Zincol-16’, ‘Barsat’, ‘NARC-2011’, and ‘Mundar’ showed superior performance when grown under different temperatures. ‘NARC-2011’, ‘Inqalab-91’, and ‘Galexy’ wheat genotypes performed well regarding of H2O2 and antioxidant activity. These genotypes had a significant level of variability under heat stress and can be used under high temperatures in future breeding programs for further research purposes.